(untitled) (Fiep Bulletin - online, 2014)
In social daily interactions there occur many acts of violence, aggressions, disrespect, arising from conflicts between people, so that education must involve the formation of human values. Considering the studies on educational sports and the formation of human values by Bracht, Broto, Craxi and Craxi, Mesquita and Migliori, the purpose was to analyze the intervention of Educational Sports in the formation of human values and to compare the internalized values reported by 85 students, of 9 and 10 years old, registered in public schools in the Municipality of Sao Paulo, who belong to the educational sports experimental group (22 students), with students that do not experience sports (control group). A mixed questionnaire was used, which proposed the following question to identify human values: "What is necessary to be a champion inside and outside the court?" Results demonstrate that 63,64% of the students of the experimental group associate the answer to the Social-affective aspect, 36,36 % to the Psychomotor and there was no indication of the Cognitive aspect. As for the control group students, 58,73 % point to the Social-affective aspect, 33,33 % to the Psychomotor aspect and 7,94% to the Cognitive one. It has been verified that the majority of students report that to be successful it is necessary to adopt the right action, peace, love, non-violence and truth. However, it is possible to identify a small superiority of indications to the Social-affective aspects of students that attend the Rexona/Ades Volleyball Project, if compared to students that are not part of the same event. Therefore, it is understood that Educational Sports may interfere with the formation of human values, although we cannot prove it, due to the fact that children cohabit in many different social environments and the complexity of social interactions they experience.